PENGGUNAAN CAMPUR KODE DALAM ACARA “CATATAN NAJWA BERSAMA MAUDY AYUNDA” DI MEDIA SOSIAL YOUTUBE - Ginting, Nismara Aulina; Efrienka, Sity Yorinda; Zamzami, Aulia Rahma (Universitas Sultan Ageng Tirtayasa, 2023)
This research was conducted with the aim of describing the form of code mixing and the context of the codes used in the event